Assessment Of Premenstrual Syndrome In Medical Students And Its Association With Progression Of Academic Years - Sadia Suboohi; Saba Pario; Ghazala Nasim; Sughra Abbasi; Shahanaz Hassan Siddiqui (Journal of Bahria University Medical and Dental College)
Objectives: The objective was to determine the frequency of Premenstrual Syndrome and its association with progression of academic years among the medical students. Study Design and Setting: A cross sectional study was conducted at United Medical and Dental College Karachi from January to June 2018 among 150 female medical students. Methodology: A structured questionnaire was designed to assess the demographic characteristics and symptoms of PMS if any experienced by the participants included in the study. The severity symptoms of PMS were marked by the participants on the behalf of their impact on their routine activity & performance, ranking from mild, moderate to severe. Data was analyzed using SPSS version 20. Results: The frequency of PMS was reported as 39% in the study participants among them 79.31% showed mild form, 17.24% showed moderate and 3.44% were diagnosed with severe PMS. Increased frequency of PMS in female medical students was observed to be associated with progression of their academic years, with final year students having highest percentage. Academic year of MBBS, type of accommodation, and occupation of mother, menstrual cycle regularity and history of PMS in family were found to be statistically significant risk factors associated with PMS. Conclusion: Premenstrual syndrome is a prevalent health issue in medical students, increasing year to year during their studies, which may unfavorably have affects on their quality of life and overall performance.